Usulan Penerapan Metode Lean Project Management Pada Pembangunan Pelebaran Gedung Gitet Cilegon Baru PT. PLN (Persero) - Sahrupi Sahrupi; Supriyadi Supriyadi; Muhammad Uzan Harisni (Universitas Mercu Buana, 2021)
The project construction of 2nd floors of GITET Cilegon Building at PT. PLN Persero run is not optimal. Delay is one of the waste occurs in the construction. This research aims to optimize the project construction with a lean thinking approach. Lean Project Management is a method used to obtain an optimal project schedule. Delay factors among others delay in material arrival, bad weather, and broken equipment. The highest risk potential was Acts of God and Natural Hazard such as rain, flood, or natural disasters. The recommendations for improvements to this problem are the switch of work that is material constrained, switch of work if any bad weather occurs. The results of the study obtained a time efficiency value of 33 days so that the work execution time could be accelerated to 156 days from the previous 189 days. The time efficiency contributes to project costs with an efficiency value of IDR 374.400.000.